Ultrasonic-template technology inducing and regulating cationic microblocks in CPAM: characterization, mechanism and sludge flocculation performance. Issue 38 (27th April 2017) - Feng, Li; Zheng, Huaili; Wang, Yili; Zhang, Shixin; Xu, Bincheng
Abstract : In this study, the ultrasonic-template polymerization technique (UTPT) was used to generate and regulate the distribution of cationic microblocks in a polymer. Abstract : In this study, the ultrasonic-template polymerization technique (UTPT) was used to generate and regulate the distribution of cationic microblocks in a polymer. The ultrasonic-template copolymer (TPAD-U) of acrylamide (AM) and methacryloxyethyl trimethyl ammonium chloride (DMC) with a novel cationic microblock structure was successfully synthesized through UTPT using sodium polymethacrylate (PMAA) as the template. Fourier transform infrared spectroscopy (FT-IR), 1 H ( 13 C) nuclear magnetic resonance spectroscopy ( 1 H ( 13 C) NMR), scanning electron microscopy (SEM) and thermogravimetric analysis (TGA) were employed to characterize the properties of the polymers. The results showed that evident cationic microblocks formed in TPAD-U. Moreover, the template polymerization mechanism and reaction kinetics were analyzed, and the results showed that the I (ZIP) mechanism and free radical termination were assigned to template copolymerization. The I (ZIP) template mechanism convincingly indicated the formation of the cationic microblocks. The sludge dewatering results demonstrated that TPAD-U showed a better sludge flocculation performance than flocculants prepared by the non-template polymerization technique. During the sludge flocculation process, the cationic microblocks in TPAD-U greatly enhanced the effects of charge neutralization and bridging, which contributed much to a prominent flocculation performance.